Chimeric RNA TNNI2-ACTA1-V1 Regulates Cell Proliferation by Regulating the Expression of NCOA3 - Liu, Dongyu; Li, Jiaxin; Hao, Wanjun; Lin, Xu; Xia, Jiqiao; Zhu, Jiyuan; Yang, Shuo; Yang, Xiuqin (Frontiers in Veterinary Science, 2022)
Chimeric RNA as an important marker provides a crucial target for tumor diagnosis and drug therapy. With the deepening of research, scholars have found that chimeric RNA also has its unique biological role in normal tissues. TNNI2-ACTA1-V1 (TA-V1), a chimeric RNA discovered by our laboratory in porcine muscle tissue, can inhibit the proliferation of Porcine Skeletal Muscle Satellite Cells (PSCs). However, the regulatory mechanism of TA-V1 in PSCs remains unclear. Based on the transcriptomic analysis results, we speculate that NCOA3, DDR2 and RDX may be the target genes of TA-V1 regulate cell proliferation. In this study, we explored the effects of NCOA3, DDR2 and RDX on cell viability and cell proliferation by CCK-8 assay, EdU staining and flow cytometry. Furthermore, the regulatory pathway of proliferation in PSCs mediated by TA-V1 through NCOA3 or CyclinD1 was elucidated by co-transfection and Co-IP. The results revealed overexpression of NCOA3 significantly increased cell viability, significantly increased the expression level of CyclinD1, and promoted cells from G1 phase to S phase, thereby promoting cell proliferation. In addition, inhibiting the expression of NCOA3 significantly reduced cell viability and inhibited cell proliferation. However, overexpression of DDR2 and RDX had no significant effect on cell viability and proliferation. Co-transfection experiments showed that NCOA3 could rescue the proliferation inhibition of PSCs caused by TA-V1. Co-immunoprecipitation (Co-IP) assay indicated that TA-V1 directly interact with NCOA3. Taken together, our study explores that TA-V1 directly regulates NCOA3, and thus indirectly regulates CyclinD1, thereby regulating PSCs proliferation. In addition, our study provides new ideas for the mechanism of porcine skeletal muscle growth and lays the foundation for the study of chimeric RNA in normal tissues.